Cognitive sex differences and hemispheric asymmetry: A critical review of 40 years of research. Issue 2 (4th March 2019) - Hirnstein, Marco; Hugdahl, Kenneth; Hausmann, Markus
ABSTRACT: According to a longstanding view, sex differences in cognitive abilities such as mental rotation or verbal memory arise from sex differences in hemispheric asymmetry: males are thought to be more lateralized than females which boosts their spatial but hampers their verbal skills. This idea sparked great interest and, even though it lost support in the 1990s, it is still put forward in contemporary (popular) scientific papers and textbooks. We aimed to provide a comprehensive review that summarizes the last 40 years of research. First, we confirm previous findings that the stronger hemispheric asymmetry in males is very small but robust. Second, we conclude that stronger hemispheric asymmetry, in general, does not enhance spatial and reduce verbal performance. Crucially, we carried out a systematic literature review showing that cognitive sex differences often emerge in the absence of sex differences in hemispheric asymmetry (and vice versa), implying the two phenomena are at least partly independent of each other. At present, there is insufficient data to conclude that sex differences in hemispheric asymmetry and cognitive performance are uncorrelated. However, we can conclude that sex differences in hemispheric asymmetry are certainly not the driving force behind sex differences in cognitive functioning.